2022
DOI: 10.34133/2022/9782562
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Treated Surfaces for VADs: From Inert Titanium to Potential Biofunctional Materials

Abstract: Objective. Laser-treated surfaces for ventricular assist devices. Impact Statement. This work has scientific impact since it proposes a biofunctional surface created with laser processing in bioinert titanium. Introduction. Cardiovascular diseases are the world’s leading cause of death. An especially debilitating heart disease is congestive heart failure. Among the possible therapies, heart transplantation and mechanical circulatory assistance are the main treatments for its severe form at a more advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…6,7 Since 1980, researchers and manufacturers VAD have incentive the development of new biomaterials and surface treatments for circulatory assistance applications; no doubt the surface modification processes can minimize thrombogenic effects on the blood, increasing the durability of an implant and the patient's life expectancy. 4,[6][7][8] The literature contains several terms that describe the hematological response to sintered titanium, such as pseudoneointima, neointimal tissue, and pannus of endothelial origin, but are not precisely defined by histological verification. In general, investigators have reported the presence of these structures as a combination of endothelial cells, fibroblasts or myofibroblasts, platelets, red blood cells, macrophages, and extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,7 Since 1980, researchers and manufacturers VAD have incentive the development of new biomaterials and surface treatments for circulatory assistance applications; no doubt the surface modification processes can minimize thrombogenic effects on the blood, increasing the durability of an implant and the patient's life expectancy. 4,[6][7][8] The literature contains several terms that describe the hematological response to sintered titanium, such as pseudoneointima, neointimal tissue, and pannus of endothelial origin, but are not precisely defined by histological verification. In general, investigators have reported the presence of these structures as a combination of endothelial cells, fibroblasts or myofibroblasts, platelets, red blood cells, macrophages, and extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…9 Since then, different modification processes have been tested, such as HeartMate® I with extruded polyurethane (PU), HeartMate II and III with sintered microspheres, Evaheart® with methacryloyphosphorylcholine (MPC) polymer, Carmeda® with heparin coating, and VentrAssist® with diamond-like carbon (DLC) coating. 8,[10][11][12][13][14] The properties of the DLC coating provide high mechanical resistance, high hardness, low coefficient of friction, chemical inertia, electrical insulating characteristic, and biocompatible substrate surface, among other characteristics capable of improving results of interaction with blood. 5 The incorporation of silver nanoparticles, for example, makes DLC bactericidal and ideal for a hospital surgical environment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations